ANALISIS PENGARUH ORIENTASI PASAR, INOVASI PRODUK, DAN KREATIVITAS STRATEGI PEMASARAN TERHADAP KINERJA PEMASARAN USAHA KERAJINAN KAYU JATI DI DESA NGLOBO KECAMATAN JIKEN KABUPATEN BLORA - fidyah yuli ernawati; siti Rochmah; Clara Fahindra s (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
This study aims to determine the effect of market orientation variables, product innovation, and marketing strategy creativity on the marketing performance of teak wood craft business in Nglobo Village, Jiken District, Blora Regency. This study uses quantitative research with a survey method that takes samples from a number of populations and uses questionnaires and interviews as the main data collection tools with a Likert scale. The data obtained were then analyzed including: validity test, reliability test, classical assumption test consisting of: normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination (R2 ). The population in this study were all teak wood craftsmen in Nglobo Village, Jiken District, Blora Regency, with a sample of 80 respondents. The sampling technique in this study is a saturated sample or a census sample, where all members of the population are sampled. The results of the multiple linear regression equation from this study are known as follows: Y = 6.234 + 0.194X1 + 0.184X2 + 0.226X3 . The results of the data analysis carried out, the indicators used in this study are all valid and reliable. For the classical assumption test, the overall data is normally distributed. The results of the t-test of this study indicate that the market orientation variable (X1) has a partial or separate effect on the marketing performance of the teak wood craft business in Nglobo Village, Jiken District, Blora Regency, with a significant value of 0.038. The market product innovation variable (X2) has a partial or separate effect on the marketing performance of the teak wood craft business in Nglobo Village, Jiken District, Blora Regency, with a significant value of 0.045. The market marketing strategy creativity variable (X3) has a partial or separate effect on the marketing performance of the teak wood craft business in Nglobo Village, Jiken District, Blora Regency, with a significant value of 0.000. The results of the analysis of the coefficient of determination (R2) in this study were 33.1%. The most influential variable on the marketing performance of the teak wood craft business in the village of Nglobo Blora is the marketing strategy creativity variable with a significant value of 0.000. The perpetrators of teak crafts in the village of Nglobo Blora need to maintain and increase the creativity of marketing strategies in marketing the products they produce.